2007
DOI: 10.1002/ijc.23184
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake and risk of breast cancer defined by estrogen and progesterone receptor status—A meta‐analysis of epidemiological studies

Abstract: The association between alcohol consumption and an increased risk of breast cancer has been established. It is still unclear however, whether this relationship differs across the estrogen receptor (ER) and progesterone receptor (PR) tumors subtypes. To provide a quantitative assessment of the association between alcohol intake and the risk of ER-/PR-defined breast cancer, we conducted a meta-analysis of cohort and case-control studies. Studies were identified by a literature search of PubMed through April 20, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 42 publications
12
113
2
3
Order By: Relevance
“…It is said ER statuses could affect the relationship of alcohol consumption with breast cancer risk (Suzuki et al, 2008), as increased estrogen and androgen levels in women consuming alcohol appear to be important mechanisms underlying the association (Breslow et al, 2011). But based on the results of our meta-analysis, ER statuses did not affect the relationship of alcohol consumption with breast cancer mortality and recurrence.…”
Section: Figure 4 Publication Bias Analysis Based Funnel Plotmentioning
confidence: 57%
See 1 more Smart Citation
“…It is said ER statuses could affect the relationship of alcohol consumption with breast cancer risk (Suzuki et al, 2008), as increased estrogen and androgen levels in women consuming alcohol appear to be important mechanisms underlying the association (Breslow et al, 2011). But based on the results of our meta-analysis, ER statuses did not affect the relationship of alcohol consumption with breast cancer mortality and recurrence.…”
Section: Figure 4 Publication Bias Analysis Based Funnel Plotmentioning
confidence: 57%
“…The association between alcohol consumption and an increased risk of breast cancer has been established (Longnecker 1994;Suzuki et al, 2008). Studies have shown that mechanisms underlying the association of alcohol intake and breast cancer risk included increased estrogen and androgen levels, enhanced mammary gland susceptibility to carcinogenesis, increased mammary carcinogen DNA damage, and greater metastatic potential of breast cancer cells (Singletary et al, 2001;Reding et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption is consistently associated with the risk of breast cancer (Deandrea et al ., 2008; MacMahon, 2006; Suzuki et al ., 2008). Alcohol feeding prompted mammary tumor formation (Wang et al ., 2012; Wong et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80% cases of human breast cancers (HBCs) are estrogen receptor positive (ER+), and ~ 20% are ER− (estrogen receptor negative) (Deandrea et al ., 2008; MacMahon, 2006; Suzuki et al ., 2008). This finding implies that ERα may play a critical role in breast cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…Options for preventing BC include removal of the target organ (i.e., prophylactic mastectomy) in very high-risk individuals (e.g., germ line BRCA1 or 2 mutations, lobular carcinoma in situ plus a strong family history) [11], chemoprevention (i.e., tamoxifen, raloxifene) for those at elevated risk (i.e., family history), and lifestyle modification (e.g., reducing weight [12] and/or alcohol consumption [13,14]) for those with an average or elevated risk, which may also have secondary health benefits.…”
Section: Preventionmentioning
confidence: 99%